An optically transparent, broadband, and highly efficient dual-mode Huygens’ transmit-array antenna based on a single-layer low-loss dielectric substrate - Longzhu Cai; Jian Deng; Jiahao Shi; Zhi Hao Jiang; Wei Hong (Materials & Design)
An optically transparent, broadband, and highly efficient dual-mode Huygens’ transmit-array antenna is proposed to address the challenge of achieving wide phase shift coverage and low transmission loss in optically transparent millimeter-wave antennas. The design is based on a single-layer low-loss dielectric substrate and metallic thin lines (MTLs). By combining two types of Huygens’ elements, a phase shift range of 383° with a transmission loss below 1.55 dB is achieved at the center frequency of 27 GHz. This approach outperforms the single-mode Huygens’ element by providing a larger phase shift range and smoother phase shift curve, using only two metal layers with minimal metallic area on a single-layer, low-loss, and optically transparent cyclic olefin copolymer (COC) dielectric substrate. Experimental results show good agreement with the simulations, and the fabricated 15 × 15-cell TA demonstrates 94 % optical transparency, a maximum gain of 24.54 dBi, an aperture efficiency of 49.7 %, and a 3-dB bandwidth of 18.5 %.